Terence Fisher - Hutchings, Peter, 1961-; Manchester University Press (Manchester, UK : Manchester University Press, 2017)
This book offers an appreciation of all of Fisher's films.
Fisher made most of the classic Hammer horrors in the 1950s and 60s including The Curse of Frankenstein and Dracula. He also had success with Gainsborough melodramas and science-fiction including The Earth Dies Screaming. Hutchings treats the Hammer horrors seriously and points out levels of complexity that have been overlooked by previous criticism. Through this book Hutchings offers a picture of Fisher's whole career while acknowledging his accomplishments as a horror-master.
Terence Fisher is best known as the director who made most of the classic Hammer horrors - including The Curse of Frankenstein, Dracula and The Devil Rides Out. But there is more to Terence Fisher than Hammer horror. In a busy twenty-five-year career, he directed fifty films, not just horrors but also thrillers, comedies, melodramas and science-fiction. This book offers an appreciation of all of Fisher's films and also gives a sense of his place in British film history. Looking at Fisher's career as a whole not only underlines his importance as a film-maker but also casts a new, interesting light on the areas in which he worked - Gainsborough melodrama, the 1950s B film, 1960s science-fiction and, of course, Hammer, one of the most successful independent film companies in the history of British cinema.
Includes bibliographical references and index.
1. Introduction 2. Fisher before horror 3. The horror man: 1957-62 4. Highs and lows: 1962-72 Conclusion Filmography Select bibliography Index.
In English.
Description based on print record.
Available through ManchesterHive.
JSTOR
Keywords: Fisher, Terence, -- 1904-1980.; Fisher, Terence, -- 1904-1980 -- Criticism and interpretation; Fisher, Terence, -- 1904-1980; PERFORMING ARTS / Individual Director (see also BIOGRAPHY & AUTOBIOGRAPHY / Entertainment & Performing Arts).; PERFORMING ARTS / Film / Direction & Production; Criticism, interpretation, etc